Congenital Dysfibrinogenemmia(Fibrinogen Giessen) - Krause, W.H; Heene, D.L; Lasch, H.G (Thrombosis and Haemostasis, 1973)
This report discusses congenital dysfibrinogenemia with facultative hemorrhagic diathesis in a 27-year-old woman patient. The autosomal-dominant hereditary transmission is assumed because of the occurrence of dysfibrinogenemia in the patient’s daughter now two-years-old. More extensive genetic examinations were impossible as the patient had been adopted.The thrombin-time, the thromboplastin- and the partial thromboplastin-time were all prolonged. Reptilase and arvin did not lead to visible coagulation. Immunologically the concentration of fibrinogen was found to be normal, but fibrinogen, when determined as a thrombin clottable protein was clearly reduced. The patient’s plasma and isolated fibrinogen had an inhibitory effect on the coagulation of normal plasma or fibrinogen. Inhibitory factors of the fibrinogen-fibrin transition or an increased fibrinolysis was not found. An isolated determination of coagulation factors gave normal results. The fibrin polymerisation of the patient’s isolated fibrin monomer was delayed and did not reach the normal maximum. By applying bidimen- sional paper electrophoresis to the patient’s isolated fibrinogen after incubation with thrombin the separation of fibrinopeptide A was shown to be absent. Plasmin applied to the pathological fibrinogen did not release any late lysis products. Based on these findings which in part differ from other reported anomalies of fibrinogen, we propose to call this variant type of fibrinogen Giessen.